Partnerships for slum improvement the ADB-JFPR and DSWD Projects in Muntinlupa City and Payatas, Quezon City - Veneracion, Cynthia Catacutan 1950-; Ayala Foundation, Inc.; Institute on Church and Social Issues; Ateneo de Manila University (Quezon City). Institute of Philippine Culture (Quezon City Institute of Philippine Culture, Ateneo de Manila University, 2004)
"This report presents the results of a process documentation research on the two pilot sites, covering over two years of field implementation, from the project launching in mid-2001 to December 2003. It also includes preproject events and activities which have implications for the implementation process."--p.3.
Chapter 1. Introduction : goals and participating organizations of the ADB-JFPR and DSWD project -- From the railroad tracks to Dreamland Heights : a partnership for urban poor relocation in Muntinlupa City -- Chapter 2. Building a community away from the railroad track -- Chapter 3. Searching for a relocation site and building new homes -- Chapter 4. Improving livelihood and organizational capabilities -- Chapter 5. Looking to the future in Dreamland Heights -- "To have an address of our own" : a partnership for slum upgrading in the Golden Shower community in Payatas -- Chapter 6. Introduction : a community's search for security of tenure -- Chapter 7. Implementing key project activities : land acquisition and site development -- Chapter 8. Providing social support services : livelihood, health, and other assistance -- Chapter 9. Beyond security of tenure : the years ahead for Golden Shower -- Initiating and sustaining partnerships for slum improvement -- Chapter 10. Concluding notes : project accomplishments and lessons learned.
A Final report submitted to the Muntinlupa Development Foundation, Vincentian Missionaries for Social Development Foundation, Inc.
Keywords: Slums -- Philippines -- Muntinlupa City; Slums -- Philippines -- Payatas (Quezon City); Poor -- Housing -- Philippines -- Muntinlupa City; Poor -- Housing -- Philippines -- Payatas (Quezon City); Community development, Urban -- Philippines -- Muntinlupa City; Community development, Urban -- Philippines -- Payatas (Quezon City)